Robust and Fast Lithium Storage Enabled by Polypyrrole-Coated Nitrogen and Phosphorus Co-Doped Hollow Carbon Nanospheres for Lithium-Ion Capacitors - Zhang, Mengdi; Zheng, Xuan; Mu, Jiawei; Liu, Pengfei; Yuan, Wenhan; Li, Shuli; Wang, Xiaobo; Fang, Haiqiu; Liu, Haiyan; Xing, Tao; Hu, Han; Wu, Mingbo (Frontiers in Chemistry, 2021)
Lithium-ion capacitors (LICs) have been proposed as an emerging technological innovation that integrates the advantages of lithium-ion batteries and supercapacitors. However, the high-power output of LICs still suffers from intractable challenges due to the sluggish reaction kinetics of battery-type anodes. Herein, polypyrrole-coated nitrogen and phosphorus co-doped hollow carbon nanospheres (NPHCS@PPy) were synthesized by a facile method and employed as anode materials for LICs. The unique hybrid architecture composed of porous hollow carbon nanospheres and PPy coating layer can expedite the mass/charge transport and enhance the structural stability during repetitive lithiation/delithiation process. The N and P dual doping plays a significant role on expanding the carbon layer spacing, enhancing electrode wettability, and increasing active sites for pseudocapacitive reactions. Benefiting from these merits, the NPHCS@PPy composite exhibits excellent lithium-storage performances including high rate capability and good cycling stability. Furthermore, a novel LIC device based on the NPHCS@PPy anode and the nitrogen-doped porous carbon cathode delivers a high energy density of 149 Wh kg−1 and a high power density of 22,500 W kg−1 as well as decent cycling stability with a capacity retention rate of 92% after 7,500 cycles. This work offers an applicable and alternative way for the development of high-performance LICs.